2018
DOI: 10.13005/bbra/2607
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Culture Media Formulations for Micropropagation of Lepisanthes fruticosa

Abstract: Tissue culture provides an avenue for the production of high quality clonal plants in large numbers within a short time. Here, we describe the development of protocols for reproducible in vitro micropropagation of Lepisanthes fruticosa via direct organogenesis. Shoots were initiated from two types of explants, nodes and young shoots, to establish in vitro cultures on Murashige and Skoog’s (MS) medium or Woody Plant Medium (WPM) supplemented with different concentrations of benzylaminopurine (BAP). Semi-solid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Data analysis for the traits in different culture media (MS, B5, WPM and, DCR) indicated that there was a significant difference between all treatments except shoot length (Table 1). Ab Rahman et al (2018) stated that the semi-solid WPM medium was most effective in shoot initiation and shoot proliferation for micropropagation of Lepisanthes Fruticosa as well. Statistical analysis showed that the effect of culture medium on root length was significant at level 5% (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Data analysis for the traits in different culture media (MS, B5, WPM and, DCR) indicated that there was a significant difference between all treatments except shoot length (Table 1). Ab Rahman et al (2018) stated that the semi-solid WPM medium was most effective in shoot initiation and shoot proliferation for micropropagation of Lepisanthes Fruticosa as well. Statistical analysis showed that the effect of culture medium on root length was significant at level 5% (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Benzyl Amino Purine (BAP) is a synthetic growth regulator of the cytokinin class which is often used in in vitro culture [5]. The use of WPM containing 1.0 mg/L BAP showed the best percentage of shoot induction rate on Lepisanthes fruticosa [6]. The use of WPM containing BAP 4 ppm + NAA 0.5 ppm showed the best results in shoot emergence time, leaf emergence time, number of leaves, root The appearance of buds is characterized by the presence of a greenish-colored bumps (multiple-bud) on the surface of the explants (Figure 1 and Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…At the same time most often most of researchers at microcloning of grapes use as basic mineral basis copy-book of the Murasige environment and Skuga (MS) [1][2][3][4][5][6][7][8][9][10]. Less often works in which authors use insignificant modifications of mineral basis of this environment [11] meet, or study against the background of MS efficiency of other standard environments [12][13][14][15][16][17]. In spite of the fact that researchers give preference in the majority of scientific works on microclonal reproduction of plants to the MS environment, this environment possesses number of the shortcomings caused by the fact that it was developed for cultivation of kallusny cells of tobacco and its main shortcoming at regeneration of meristems is high concentration of salts of 4.7 g/l.…”
Section: Introductionmentioning
confidence: 99%